2016
DOI: 10.2340/00015555-2437
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2 is Involved in Itch-associated Responses in Mice with Atopic Dermatitis-like Skin Lesions

Abstract: To investigate the mechanisms underlying itching in atopic dermatitis, we examined whether thromboxane (TX) A2, an arachidonic acid metabolite, is involved in spontaneous scratching, an itch-related response, in NC mice with atopic dermatitis-like skin lesions. The TXA2 receptor (TP) antagonist ONO-3708 inhibited the spontaneous scratching. The mRNA expression of TX synthase (TXSyn) distributed mainly in epidermis and the concentration of TXB2, a metabolite of TXA2, were increased in lesional skin. Scratching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Interestingly, the reduction on skin DHA and EPA has been associated with alteration in the epidermal barrier [13] , the decrease in PD1, PGF 1 , KETE and EET with inflammation [3] , [14] , [15] , TXB 2 indicating lesions [15] and 12-HHT through BLT2 receptor, has been described as a pro regenerative lipid mediator [16] . On the other hand, the local increase of PGD 2 , PGE 2, and HODEs has been associated with hair loss, inflammation and oxidative stress [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reduction on skin DHA and EPA has been associated with alteration in the epidermal barrier [13] , the decrease in PD1, PGF 1 , KETE and EET with inflammation [3] , [14] , [15] , TXB 2 indicating lesions [15] and 12-HHT through BLT2 receptor, has been described as a pro regenerative lipid mediator [16] . On the other hand, the local increase of PGD 2 , PGE 2, and HODEs has been associated with hair loss, inflammation and oxidative stress [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, TXA 2 produced from epidermal keratinocytes is involved in spontaneous scratching in mice with dermatitis. 16 In this study, a-MSHeinduced scratching was inhibited by a TP receptor antagonist. Therefore, it is suggested that TXA 2 plays an important role in a-MSHemediated scratching in mice with dermatitis.…”
Section: Discussionmentioning
confidence: 67%
“…24 TP receptors are expressed in primary afferent neurons, and the activation of TP receptors increases the concentration of intracellular Ca 2þ ions. 12,16 Therefore, TXA 2 produced from a-MSHe stimulated keratinocytes directly acts on primary afferent neurons and elicits scratching. The DRG is an accumulation of cell bodies of primary afferent neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other data suggest that PAR2 may perpetuate inflammatory pain and promote inflammation through a neurogenic mechanism . PAR2 pain and itch pathways seem to be mediated by the TRP channels and upregulated pruritogens such as thromboxane A2, leukotriene B4 and prostaglandin E2 …”
Section: Introductionmentioning
confidence: 99%